(untitled) (Nigerian Journal of Technology, 2018)
The complex environment of the Sun-Earth, which resulted in the spatial and temporal variations of the ionosphere leads to different kinds of effects on human technologies. Man’s continuous increasing utilization of space technologies in addressing it’s immediate and future needs demand quality research of the space environments, to understand the physics of the interaction of the environment with systems (both space and earth bound), and to develop methods of mitigating the environmental effects. This is one of the reasons Center of Atmospheric Research (CAR) set-up a GNSS monitoring station in Benin. The Vertical Total Electron Content (VTEC) time series of some selected days from the newly established Benin station together with three Cors stations (ABU, BKFP and CLBR) of OSGoF were subjected to the Lloyd seasonal classification in order to see their diurnal variation on season by season bases. The results show that there exist an interconnection(in term of their magnetic longitudes) between the ABU, CLBR and the BENIN stations even though BENIN station had the least Total Electron Content (TEC) values at all the seasons. The results also clearly showed that the BENIN station offers better advantage in terms of positional accuracy. http://dx.doi.org/10.4314/njt.v37i2.1